Soil-plant interactions in the high-altitude ecosystems: A case study from kaz daği (Mount Ida), Turkey - (:unkn) unknown (Springer International Publishing, 2015)
Kaz Daği, the ancient Mount Ida, is a mountainous area and one of the important biodiversity spots, located in the north of Edremit in northwestern Anatolia. The area abounds in fertile soils, wetlands, underground resources, favorable climatic conditions, interesting geomorphological characteristics, and several world famous archeological and cultural places. Southwestern part of the mountain has been declared as a national park in 1993, which hosts a very rich and diverse flora including many endemic and rare species; a majority of these are of great economical and ethnobotanical significance. Attempts were therefore made to investigate the changes in the soil mineral elements at different altitudes within the park, in order to evaluate their potential effects on the flora of Kaz Dagi high-altitude ecosystem. Soil samples were thus collected from different localities at every 100 m elevation on the road to the national park and along the path leading to Sarikiz Hill inside the park. It was observed that B, Ca, Cu, Mg, Mn, and Ni have lower concentrations at lower elevations; however, with increasing elevations the concentrations increase to a certain point and then show a decrease again reaching the lowest values at the elevations of 1600-1700 m. Our studies have revealed the fact that the altitudinal variations (100, 600, 1000, and 1600-1700 m) have great relevance to the elemental distribution in the soils of Kaz Dagi. Keeping in view different climate scenarios put forward, there will be interferences on the plant diversity as well as soil-plant interactions related to this aspect. The topic has been evaluated in the light of these expectations. © Springer International Publishing Switzerland 2015.
Keywords: Climate impacts; Kaz Daği; Plant diversity; Soils